Catalyst-free organic synthesis - Brahmachari, Goutam (Royal Society of Chemistry, 2018)
Explaining methods for carrying out chemical syntheses without the use of catalysts, this book shows how avoiding catalysts during synthesis can mean less use of toxic chemicals, environmentally damaging chemicals, or endangered elements, and lower costs.
Keywords: Organic compounds -- Synthesis.; elektronické knihy; electronic books